Cattle Breeding under Climate Change - Markiian KUZIV; Nataliia KUZIV; Yelyzaveta FEDOROVYCH; Vitaliy FEDOROVYCH; Nataliya MAZUR (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine)
Climate change occurring on our planet is one of the key risks that negatively affect and will continue to affect the economic development of the livestock industry. The purpose of this review is to summarize the literature on cattle breeding in the context of climate change. The study material consisted of an analysis of selection and breeding practices in cattle farming based on literature sources. The conservation, use, and genetic improvement of local breeds should be one of the strategic directions of livestock development, while specialized breeds should be improved not only for their productive characteristics but also for their adaptation to climate change. Genetic selection for thermo-resistance is potentially a sustainable approach to mitigating the negative impact of heat stress on animal productivity. The genetic correlation between thermo-resistance and other economically important traits that should be considered in breeding will allow for increased productivity while enhancing animal resilience. Genomic selection will play an important role in mitigating the negative effects of climate change on livestock and should be intensified based on already identified biomarkers controlling heat stress regulation and animal productivity. Therefore, maintaining animal genetic diversity will be crucial for ensuring food security.